Evaluación de la problemática de los residuos sólidos urbanos en el municipio de la ciudad de Moyobamba - Vela Ramírez, Anyella Karina (2015)
This final report of the thesis, presented the activities undertaken and results obtained from the execution of the thesis entitled "ASSESSMENT OF THE PROBLEMATIC OF THE URBAN SOLIO WASTE IN THE MUNICIPALITY OF MOYOBAMBA CITY, 2014 ", whose specific objectives were: ldentify the generation sources of municipal salid waste (MSW) in Moyobamba city, analyze the current situation of the village in the area of urban salid waste and analyze the site municipal disposal of municipal salid waste and identify clandestine dumps. The present report provides details on the approach of the research problem, the methodological framework used in the implementation of the project and finally on the results obtained. With the implementation of the project has reached the following conclusions: • With respect to the sources of generation of municipal solid waste in Moyobamba city, it was able to conclude the following: ./ That the generation of salid waste in Moyobamba city is 0.64 kg/inhab.day causing 56.40 Tn/day. These residues have a volumetric weight of 230.44 kg/m3 and its components (by weight), is given by organic matter (77.46 % ), the waste not exploitable bags and plastic packaging (3.51 % ), remnants from hygiene services (7.62% ), the ash and other to the left 0.63% and the hazardous waste remnants of broken bulbs medicine and 0.17 per cent and in them we find usable waste such as plastics, paper, ferrous metals . ./ That the population is not aware about the excessive generation of salid waste that is being generated in Moyobamba city, but if they have the predisposition of support in the integral management of residential salid waste, with the purpose of diminishing the generation of salid residues, with what it can indicate that the decrease of the generation of salid residues in Moyobamba city to domiciliary level can get improved substantially with base in programs of environmental education for a more suitable utilization of the by-products. • On the current situation of the municipality as for solid urban residues, it is possible to conclude that: ./ That a disregard for the management of salid waste from the town, this due to a lack of awareness, funding sources, deficiency in environmental training and education, you can determine that the Moyobamba Provincial Municipality has no system of integrated salid waste management, being the stage of collection, transfer and disposal the most critica!, still necessary implementing corrective measures and guidelines to be followed to obtain improvements with regard to the issue in favor of the community. • To The respect of the site of final disposal of solid waste municipal urban and identify clandestine dumps, it was concluded that: ./ That the municipality is arranging their salid waste at a junkyard Jocated 5 km from the Moyobamba city, by what you need to implement or execute projects for the construction of sanitary Jandfills . ./ Well same by excessive production of salid waste and lack of a process of segregation and recycling in the establishments (markets, trade and other) causes an increase in the amount in the salid waste dumps that they are for the most part the ravines, streets and parks of Moyobamba city, causing the presents 12 CRITICAL POJNTS, proliferated of diseases. Therefore, it is necessary to promote projects to public or private level for the construction of infrastructure for final disposition. Key words: urban salid waste; integral management.